Penyelesaian Sengketa Antara Indonesia Dan Australia Dalam KasusPencemaran Laut Timor Akibat Tumpahan Minyak Montara - Doni Adi Supriyo; Rusito (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2022)
This paper aims to analyze the responsibility of Australia and Thailand for cases of pollution from the leakageof the Montara oil well which is owned by a Thai company. This pollution originates from the Montara Field TheMontara Well Head Platform in the West Atlas Block ofthe Timor Sea in Australian waters. The oil spill resultedin cross-border pollution because it extended to the waters of the Timor Gap or Timor Gap which is the borderwaters between Indonesia, Australia and Timor Leste (Meinarni, Volume 5). The extent of the effect of oil spillcontamination from the well located in the Northwest Atlas Block of Timor is about 75% entering Indonesianwaters, so this pollution is an important problem for the Indonesian people, because it enters the ExclusiveEconomic Zone (EEZ). This writing is writing that uses normative legal research using a statutory approach,concept approach, and case approach in accordance with the legal perspective of the United NationsConvention on the Law of the Sea 1982 and relevant legal theories that will be used and constructed. with legalprinciples, principles and doctrines. Based on Article 139 Paragraph (1) of UNCLOS 1982, the State must beresponsible for activities carried out in the marine area, whether by participating States, individuals or statecompanies or legal entities or individuals who have the nationality of their country